Cyclists’ Anger As Determinant of Near Misses Involving Different Road Users - Marín Puchades, Víctor; Prati, Gabriele; Rondinella, Gianni; De Angelis, Marco; Fassina, Filippo; Fraboni, Federico; Pietrantoni, Luca (Frontiers in Psychology, 2017)
Road anger constitutes one of the determinant factors related to safety outcomes (e.g. accidents, near misses). Although cyclists are considered vulnerable road users due to their relatively high rate of fatalities in traffic, previous research has solely focused on car drivers, and no study has yet investigated the effect of anger on cyclists’ safety outcomes. The present research aims to investigate, for the first time, the effects of cycling anger toward different types of road users on near misses involving such road users and near misses in general. Using a daily diary web-based questionnaire, we collected data about daily trips, bicycle use, near misses experienced, cyclist’s anger and demographic information from 254 Spanish cyclists. Poisson regression was used to assess the association of cycling anger with near misses, which is a count variable. No relationship was found between general cycling anger and near misses occurrence. Anger towards specific road users had different effects on the probability of near misses with different road users. Anger towards the interaction with car drivers increased the probability of near misses involving cyclists and pedestrians. Anger towards interaction with pedestrians was associated with higher probability of near misses with pedestrians. Anger towards cyclists exerted no effect on the probability of near misses with any road user (i.e., car drivers, cyclists or pedestrians), whereas anger towards the interactions with the police had a diminishing effect on the occurrence of near misses’ involving all types of road users. The present study demonstrated that the effect of road anger on safety outcomes among cyclists is different from that of motorists. Moreover, the target of anger played an important role on safety both for the cyclist and the specific road users. Possible explanations for these differences are based on the difference in status and power with motorists, as well as on the potential displaced aggression produced by the fear of retaliation by motorized vehicle users.